Parageneses of cryogenic formations of gas emission funnels (Part 2). Cryogenic factor in formation of gas funnels - Khimenkov, Aleksandr Nikolaevich; Koshurnikov, Andrei Viktorovich; Stanilovskaya, Julia Viktorovna (Арктика и Антарктика, 2021)
The subject of this research is frozen rocks that compose gas emission funnels in the north of Western Siberia. The object of this research is the cryogenic factor that causes the formation of gas emission funnels. The authors substantiate the thesis that gas emission funnels are cryogenic phenomenon, and the processes preparing the explosion cannot be accurately interpreted without taking these features into account. The analysis of research materials on gas emission funnels, discovered in the north of Western Siberia, allows concluding that surface conditions may have a significant impact upon the formation of gas emission funnels. Special attention is given to consideration of the hypothesis of formation of gas emission funnels due to local heat penetration and gas supply from the depth. The necessary conditions are described. The article provides the examples of using geophysical methods for detecting of gas supply channels. It is concluded that gas emission funnels are the result of self-development of fluid-dynamic geosystems, which represent local, ice subsurface gas-saturated formations that are in a inequilibrium thermodynamic state with respect to the enclosing permafrost formations. The authors' special contribution consists in examination of the external and hidden mechanisms of the emergence of inequilibrium conditions od the mechanism that launches an explosion. The novelty of this research lies in the development of technique for determining the processes that cause the emission of underground gas, based on the analysis of cryogenic formations, which compose the walls of gas emission funnels.